Compact dual segment cylindrical dielectric resonator antenna for X-band applications - Sahu B.; Singh R.; Singh S.P.; Tripathi P. (My University, 2025)
The simulation and experimental studies of a compact dual segment cylindrical dielectric resonator antenna (DRA) for X-band applications are presented in this paper. The antenna consists of Teflon (εr = 2.1) as lower segment and ceramic material (Sr La2 Mg2 W2 O12) of dielectric constant εr = 22 and loss tangent tan δ = 0.0021 as upper segment. The simulation study of the antenna is carried out using Ansoft's HFSS software. Parametric study of the antenna has been carried out by varying the Teflon and probe heights. The simulated and measured bandwidths of the proposed antenna are 1.11 GHz and 1.69 GHz respectively whereas corresponding values of average gain are 6.39 dB and 6.43 dB. The broadside radiation patterns are obtained (in both E-and H-planes) in the applicable frequency range with fairly low cross-polarization levels in E-plane. The experimental results are in good agreement with simulated results. © 2013 IEEE.